2021
DOI: 10.1038/s41536-021-00185-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of human endothelial colony-forming cells and mesenchymal stromal cells exert neuroprotective effects in the growth-restricted newborn

Abstract: The foetal brain is particularly vulnerable to the detrimental effects of foetal growth restriction (FGR) with subsequent abnormal neurodevelopment being common. There are no current treatments to protect the FGR newborn from lifelong neurological disorders. This study examines whether pure foetal mesenchymal stromal cells (MSC) and endothelial colony-forming cells (ECFC) from the human term placenta are neuroprotective through modulating neuroinflammation and supporting the brain vasculature. We determined th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…However, this treatment did not significantly reduce the increased number of astrocytes present in the brain parenchyma of the FGR piglet. 124 These results are again corroborated by an FGR lamb study where UCB treatment reduced activated microglial cells but had no effect on astrocytes. 123 Furthermore, an FGR rat study also showed that umbilical cord-derived mesenchymal stromal cells (UC-MSC) did not affect the number of astrocytes 7 days after treatment.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…However, this treatment did not significantly reduce the increased number of astrocytes present in the brain parenchyma of the FGR piglet. 124 These results are again corroborated by an FGR lamb study where UCB treatment reduced activated microglial cells but had no effect on astrocytes. 123 Furthermore, an FGR rat study also showed that umbilical cord-derived mesenchymal stromal cells (UC-MSC) did not affect the number of astrocytes 7 days after treatment.…”
Section: Introductionsupporting
confidence: 54%
“…This suggests that eECFC treatment improves brain vasculature without promoting excessive angiogenesis. 124 The same study showed BBB integrity was also improved following cECFC treatment in the FGR piglet with reduced albumin leakage into the brain. 124 Conversely, MSCs delivered alone did not exert a significant effect on improving the vasculature in the brains of FGR piglets 3 days after treatment.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations